PREPARATION OF COBALT DECORATED TITANIUM DIOXIDE NANOTUBES BY ELECTRODEPOSITION - Ismail, S.; Abu Bakar, F.I.; Lee Yen, B.A.W.; Eshak, Z.; Rozana, M. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
In the present study a cobalt decorated titanium dioxide (TiO2) nanotube arrays photocatalyst with varying dopant concentration of cobalt chloride (0.01 mM, 0.05 mM and 0.1 mM) and deposition time (1 min, 2 min and 3 min) were synthesized by electrodeposition method. The sample produced were characterized by X-ray Diffraction (XRD), Raman Spectroscopy (RAMAN), Scanning Electron Microscope (SEM), and UV-Vis absorption spectra (UV-Visible) technique. Methyl orange dye was used as the environmental pollutant probe. The photocatalytic performance of the synthesized photocatalysts was evaluated under the UV irradiation sources. The optimum concentration of cobalt chloride of 0.05 mM gives better decoration of cobalt on TiO2. Furthermore, it reveals that the highest degradation activity under UV irradiation can be up to 60%. While, excess of cobalt (Co) decorated on TiO2 suppressed the photocatalytic of TiO2 as well as forming lumps on the TiO2 due to agglomeration. Hence, these contributed to the reduction of effective surface sites and the degradation of dye become limited.